Upconversion studies of Ho3+ activated tellurite glasses under the sensitization of Yb3+ ions - K. Suresh; C. K. Jayasankar; Wisanu Peccharapa (My University, 2018)
Holmium (Ho3+)/ytterbium (Yb3+) co-doped tellurite glasses of different concentrations were prepared by deploying melt quenching technique. The upconversion spectra of the Ho3+/Yb3+ co-doped tellurite glasses were measured under excitation of 980 nm diode laser (Yb3+: 2F7/2→2F5/2). The glasses have exhibited three emission peaks attributed to the Ho3+: 5F4→5I8 (551 nm), 5F5→5I8 (661 nm) and 5F4→5I7 (758 nm). Among these three transitions, the transition corresponding to the 661 nm emission is found to be strongest for all the concentrations. The emission intensities of Ho3+ ions are found to be continuously increased upto 5.0 mol % co-doping of Yb3+ ions and no luminescence quenching was observed. The decay times of 5F5 levels of Ho3+ ions are measured in all the co-doped glasses by monitoring the emission at 661 nm. The decay profile of the curves is found to be single exponential in nature.
Keywords: Photon Upconversion; Holmium; Ytterbium; Glass properties and applications